Development and Validation of an Instrument to Assess Lecturers' Verbal and Nonverbal Communication in Promoting Students' 4C Skills - Adhi Kusuma; Artika Sari; Deni Iriyadi; Deni Ramdani (Universitas Negeri Makassar, 2026)
The era of Society 5.0 demands college tall For produce graduates who have skills 21st century, especially the 4Cs (critical thinking, creativity, communication, collaboration). In the context of said, the ability verbal and nonverbal communication of lecturers become element strategic determining quality interaction learning as well as success student in develop skills said. Research This aim develop instrument measurement ability verbal and nonverbal communication of lecturers in equip student with 4C skills. Research use Research and Development (R&D) method with the 4-D development model (Define, Design, Develop, Disseminate). Validity content tested through expert judgment and calculated using the Content Validity Index (CVI), while validity construct tested using Confirmatory Factor Analysis (CFA). The research results show that all instrument items declared valid and reliable, with the factor loading value is in the range of 0.61–0.87 and fulfillment part big goodness of fit criteria. Instrument This in a way overall capable describe quality verbal and nonverbal communication of lecturers in the learning process. Findings study indicates that ability communication lecturer contributes significant to strengthening 4C skills of students and become factor important in increase quality learning at college high in the Society 5.0 era. The instruments developed can used as base evaluation as well as development of improvement programs competence communication lecturers for better learning humanistic, interactive, and transformative. @font-face font-family:"Cambria Math"; panose-1:2 4 5 3 5 4 6 3 2 4; mso-font-charset:0; mso-generic-font-family:roman; mso-font-pitch:variable; mso-font-signature:-536870145 1107305727 0 0 415 0;@font-face font-family:Calibri; panose-1:2 15 5 2 2 2 4 3 2 4; mso-font-charset:0; mso-generic-font-family:swiss; mso-font-pitch:variable; mso-font-signature:-536859905 -1073732485 9 0 511 0;p.MsoNormal, li.MsoNormal, div.MsoNormal mso-style-unhide:no; mso-style-qformat:yes; mso-style-parent:""; margin-top:0cm; margin-right:0cm; margin-bottom:10.0pt; margin-left:0cm; line-height:115%; mso-pagination:widow-orphan; font-size:11.0pt; font-family:"Calibri",sans-serif; mso-fareast-font-family:"Times New Roman"; mso-bidi-font-family:"Times New Roman"; mso-ansi-language:EN-US; mso-fareast-language:JA;.MsoChpDefault mso-style-type:export-only; mso-default-props:yes; font-size:10.0pt; mso-ansi-font-size:10.0pt; mso-bidi-font-size:10.0pt; font-family:"Calibri",sans-serif; mso-ascii-font-family:Calibri; mso-fareast-font-family:Calibri; mso-hansi-font-family:Calibri; mso-font-kerning:0pt; mso-ligatures:none;div.WordSection1 page:WordSection1;